One-Year Evaluation of a Simplified Ethanol-Wet Bonding Technique: A Randomized Clinical Trial - Araujo,Joyce Figueira de (2013)
The objective of this randomized clinical trial was to evaluate the clinical performance of adhesive restorations using a three-step etch-and-rinse adhesive (TSER), a one-step self-etching adhesive (OSSE), and a simplified ethanol-wet bonding technique (EWBT) prior to the application of a composite resin in non-carious cervical lesions. Ninety-three restorations (31 for each group) were placed in 17 patients by a single operator. No cavity preparation was performed. After 6 and 12 months, the restorations were assessed by two previously trained examiners using modified Ryge criteria for retention (kappa=1.00) and marginal adaptation/staining (kappa=0.81), and the results were analyzed by Fisher's exact and Kruskal-Wallis tests, respectively. No significant differences were observed among groups at the 6- and 12-month time points for any of the assessed criteria (p≥0.05). The intra-group analysis performed by Cochran's test (for retention) and Wilcoxon test (for marginal adaptation/staining) revealed significant differences between the baseline/12-month time intervals in marginal adaptation in OSSE (p=0.0180) and in marginal staining in TSER (p=0.0117). The survival analysis for retention criteria performed using a log-rank test did not show significant differences (p>0.05). The restorations placed using the simplified EWBT performed equally well as the other adhesive strategies employed.